Utilization of Fly Ash Palm Oil Mill Waste as an Adsorbent of Methylene Blue in a Fixed Bed Column System by Using Response Surface Methodology - Sylvia, Novi; Dewi, Rozanna; Ishak, Ishak; Janni, Miftahul; Putri, Melani Annisa (Universitas Negeri Semarang, 2024)
Palm kernel shell combustion waste in boiler units called fly ash (FA) is a low-cost alternative material as an adsorbent. FA contains high levels of silica (SiO2) and aluminium oxide (Al2O3). The content of both compounds is an important component as an adsorbent. FA was used to absorb methylene blue (MB) continuously from synthetic dye wastewater. The study was conducted by continuous system process optimization using Response Surface Methodology (RSM) Box-Behnken design. MB was flowed on a set of fixed-bed adsorption columns with independent variables in this study are X1 (bed height; 8, 12, 16 cm), X2 (contact time; 90, 120, 150 min) and X3 (flow rate; 2, 4, 6L/min). The dependent variables were Y1 (removal efficiency) and Y2 (adsorption capacity) with matrix design by Box-Behnken. Optimisation of MB removal in this study was obtained at X1 = 16 cm, X2 = 150 min and X3 = 2 L/min with removal efficiency of 98.45% and adsorption capacity of 0.115 mg/g. FA pores according to SEM analysis were obtained at 1-2 µm. Likewise, the results of EDX analysis showed that there were N and Cl atoms in FA after the adsorption process. This shows that FA is able to adsorb MB.